Efficiency of I-gel supraglottic airway device during mechanical ventilation in supine and lateral decubitus position in obese patient; prospective observational study. Issue 1 (1st January 2020) - Farouk, Inas; Abdelhamid, Bassant Mohamed; Wishahy, Mohamed Kadry; Mohamed, Hassan; Hassan, Mohamed Mahmoud
ABSTRACT: Background: I-gel supraglottic airway device has been widely used recently in anesthesia practice as an alternative to endotracheal intubation. However, its safety and feasibility in obese patients are still under investigations. The aim of this work was to evaluate the efficiency of I-gel in supine and lateral position in adult obese (BMI 30–40) mechanically ventilated patients undergoing short surgical procedures (60 − 120 min). Methods: Prospective observational study was conducted at Kasr Alainy Hospital. A total of 40 obese patients with body mass index 30–40 aged between 20 and 60 years, American Society of Anesthesiologists class II & III scheduled for elective surgeries were enrolled in one group. We used the I-gel in supine position and lateral position in the same patient. The primary outcome was comparison between Oropharyngeal leak airway pressure during controlled ventilation in supine position after insertion of I-gel by 1 min and in lateral position. The secondary outcomes were fiberoptic view, insertion attempts and postoperative upper airway complications Results: The leakage pressure required for I-gel did not show statistically significant difference between both supine and lateral positions (33.88 ± 7.34 cmH2 O versus 33.10 ± 7.58 cmH2 O) respectively. Fiberoptic view ranged between score 2 (8 patients) and score 3 (32 patients) in both supine and lateral position. I-gel was inserted in the first trial in 37 patients, the second trial in two patients and the third trial in one patient. None of the patients experienced postoperative swallowing difficulties, throat pain, hoarseness or postoperative nausea and vomiting. Only two patients (5%) showed blood on I-gel after removal. Conclusion: The use of I-gel supraglottic airway device is safe and effective in both supine and lateral position in obese patients under mechanical ventilation with reliable ventilation and no postoperative airway complications. Clinical trial registration: clinicaltrial.gov. ID: NCT04119245